VERBAL EFFECT OF MEANING COMPLETION (Psychology Travelogs, 2025)
The aim of the study was to determine the peculiarities of verbal dynamics in relation to the process of information comprehension. Particularly it was planned to determine the existence of the verbal effect in different age groups in the case of completing a cognitive task. The «Method of text breaks» was used in the empirical study. It was found that verbal activity dynamics increase in all age groups, especially in the youth group, but decrease with age. Semantic completion is marked by an increase in the number of words. This suggests that higher levels of verbal productivity upon task completion are related to the effect of adaptation to the specifics of its implementation. At the same time, the semantic complexity increases. This may indicate the activation of cognitive processes in its final stage of study. Verbal activity and semantic complexity were directly, but not strongly, correlated. This relationship varies with age and shows a more distinct trend at the beginning of the cognitive task, whereas by the end of the task, this trend becomes weaker. Obviously, this can be explained by the fact that the semantic indicator does not increase as much as the verbal one. The decline in the relationship between verbal productivity and semantic complexity is particularly apparent in middle and old age. The youth and young adult groups demonstrate the most stable results in verbal productivity and semantic complexity, which is reflected in the increase in indicators upon completing the cognitive task of the specified type. The younger groups demonstrate higher levels of cognitive productivity, which tend to increase, whereas the older age groups show greater variability. However, it should be noted that only the results in the youth group are normally distributed.
Keywords: cognitive activity; cognitive dynamics; verbal productivity; semantic weight; meaning